Towards a Jewish-Christian-Muslim theology - Burrell, David B. (Challenges in contemporary theology., 2011)
"Towards a Jewish-Christian-Muslim Theology delineates the ways that Christianity, Islam, and the Jewish tradition have moved towards each another over the centuries and points to new pathways for contemporary theological work. Explores the development of the three Abrahamic traditions, brilliantly showing the way in which they have struggled with similar issues over the centuries. Shows how the approach of each tradition can be used comparatively by the other traditions to illuminate and develop their own thinking. Written by a renowned writer in philosophical theology, widely acclaimed for his comparative thinking on Jewish and Islamic theology. A very timely book which moves forward the discussion at a period of intense inter-religious dialogue"--